2003
DOI: 10.1124/dmd.31.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Alterations of Canalicular Membrane Transport Activities in Rats with CCl4-induced Hepatic Injury

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The influence of CCl 4 -induced experimental hepatic injury (CCl 4 -EHI) on the expression and transport activities of primary active transporters on the canalicular membrane, including P-glycoprotein (P-gp), a bile salt export pump (Bsep) and a multidrug resistance associated protein2 (Mrp2), was assessed. CCl 4 -EHI was induced by an intraperitoneal injection of CCl 4 to rats at a dose of 1 ml/kg 24 h prior to the preparation of canali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The expression of multidrug-resistance related protein (Mrp2) is not affected for hepatic microsomes (14), whereas a significant decrease is observed for the canalicular membrane (15). In addition, our previous studies has revealed that the in vitro transport of organic cations across the sinusoidal membrane is decreased as a result of CCl 4 -EHI (16), while the transport activity of Pglycoprotein (P-gp) in the canalicular membrane is increased by CCl 4 -EHI (15).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The expression of multidrug-resistance related protein (Mrp2) is not affected for hepatic microsomes (14), whereas a significant decrease is observed for the canalicular membrane (15). In addition, our previous studies has revealed that the in vitro transport of organic cations across the sinusoidal membrane is decreased as a result of CCl 4 -EHI (16), while the transport activity of Pglycoprotein (P-gp) in the canalicular membrane is increased by CCl 4 -EHI (15).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of daunorubicin in plasma, bile and urine, as well as those of daunorubicinol in plasma, were quantified by HPLC with a fluorescence detector, as previously described (15). Briefly, a 100-µL aliquot of the biological samples (i.e., plasma, bile, and urine) was deproteinized by adding 250 µL of methanol and 1 mL ethyl acetate and centrifuging at 10,000 rpm for 5 min.…”
Section: Hplc Assay Of Daunorubicin and Daunorubicinolmentioning
confidence: 99%
See 3 more Smart Citations